Total, dietary, and supplemental calcium intake and risk of all-cause cardiovascular, and cancer mortality: a systematic review and dose-response meta-analysis of prospective cohort studies. Issue 21 (19th July 2022) - Naghshi, Sina; Naemi, Mohammad; Sadeghi, Omid; Darooghegi Mofrad, Manije; Moezrad, Mehrasa; Azadbakht, Leila
Abstract: Considerable controversy exists regarding the association between calcium intake and mortality risk. Therefore, this study aimed to summarize available findings on the associations of total, dietary and supplemental calcium intake with all-cause, CVD, and cancer mortality. We searched PubMed, Scopus, Embase, and ISI Web of Knowledge until February 2020 to identify eligible publications. Random-effects models were used to calculate pooled effect sizes (ESs) and 95% confidence intervals (CIs) for highest versus lowest categories of calcium intake and to incorporate variation between studies. Linear and non-linear dose-response analyses were done to evaluate the dose-response relations between calcium intake and mortality. 36 publications were included in this systematic review and 35 in the meta-analysis. During the follow-up periods ranging from 4.2 to 28 years, the total number of deaths from all causes was 163, 657 (83703 from CVD and 83929 from cancer). Total calcium intake was associated with a lower risk of CVD mortality (Pooled ES for highest v lowest category: 0.91; 95% CI: 0.83–0.99, I 2 =68.1%, P  < 0.001). Dietary calcium intake was associated with a lower risk of all-cause mortality (Pooled ES for highest v lowest category: 0.95; 95% CI: 0.92–0.99, I 2 =62.1%, P  < 0.001). Supplemental calcium intake was not significantly associated with risk of all-cause, CVD and cancer mortality. In the dose-response analysis, there was evidence of nonlinear association between calcium intake and risk of all-cause, CVD, and cancer mortality. In conclusion, a non-linear association between calcium intake with all-cause, CVD, and cancer mortality risk was observed in this meta-analysis. Moderate intake of total (1000–1800), dietary (600–1200), and supplemental calcium (600–1200) was inversely significantly associated with mortality risk but higher calcium intake was not associated with a lower risk of mortality.